(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The purpose of this study was to analyze the Effect of Distributive Justice, Procedural Justice and Interactional Justice on Teacher Engangement and Teachers Performance. The method used in this research is quantitative methods, data collection methods by distributing online questionnaires to teachers in Tangerang. Tools for processing data is by using PLS and using SmartPLS version 3.0 software. The questionnaires were distributed electronically with simple random sampling technique and the questionnaires returned were 180 respondents. Based on the results of the research data analysis, it can be concluded that distributive justice has no significant effect on teacher engagement. procedural justice has a significant effect on teacher engagement, interaction justice has no significant effect on teacher engagement, distributive justice has no significant effect on teachers performance. procedural justice has no significant effect on teachers performance. Interactional justice has a significant effect on teachers performance. teacher engangement has no significant effect on teachers performance. The expected contribution from this research is expected to be able to expand knowledge and become literature as a guide in improving employee engagement and teacher performance, can provide contributions and thoughts for leaders and management at schools to make policies in spurring teacher engagement and performance.